(untitled) (Palíndromo, 2022)
The pandemic has put us against the imminence of the end of the world. The images of the end are manifested in dreams crossing the western imagination. How can the West think beyond itself? Based on the readings of Ailton Krenak and Davi Kopenawa, we seek to analyze dreams as another way of knowledge and relationship with reality. For this, two concepts are fundamental in Ailton Krenak’s critique of Western civilization: humanity and the world. The idea of ​​homogeneous humanity, separated from the world, has led to the end of the different worlds that coexist on Earth. As the world has already ended for the native communities who were exterminated. Faced with the ends of the worlds, from the fall of the sky, we can learn from Yanomami dreams to holding up the sky as a way of postponing the ends. Thus, the politics of Amerindian dreams provide us with other perspectives on the transformation of bodies and reality in the long contemporary night of insomnia and political nightmares.